Food environments: Improving their healthfulness - Fretes, Gabriela; Marshall, Quinn; Leroy, Jef L. (International Food Policy Research Institute, 2024)
The food environment is the setting in which people choose what to eat, where they buy those foods, and where, when, and how they eat. This chapter examines some of the key challenges and opportunities for food environments amid the rapid transitions occurring in low- and middle-income countries. It presents examples of evidence-based food environment policies and actions that are being implemented to promote diet quality in a diverse range of countries. The conclusions reflect on potential policies for improving diets through changes in food environments, and discuss actions needed to move forward in strengthening the healthfulness of food environments.